ANALYSIS OF MENTZER INDEX IN CHILDREN PRESENTING WITH MICROCYTIC HYPOCHROMIC ANEMIA: A CROSS-SECTIONAL STUDY - ARINDAM GHOSH; DEBDEEP DASGUPTA; SUSUMNA BISWAS (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study was to analyze Mentzer index in pediatric patients presenting with microcytic anemia. Methods: This was a cross-sectional study conducted in the Department of Physiology of a tertiary care medical institute. One hundred and twenty children below the age of 12 years and having microcytic hypochromic anemia were included in this study on the basis of predefined criteria. Mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), MCH concentration (MCHC), and Mentzer index were analyzed from complete blood count reports. Those with a Mentzer index more than 13 were advised further workup to rule out possibility of thalassemia. SPSS 22.0 software was used for statistical analysis and p<0.05 was taken as statistically significant. Results: Out of 120 studied cases, there were 71 (59.17%) boys and 49 (40.83%) girls. There was a male predominance among the studied cases with M: F ratio being 1:0.69. The mean age of boys (8.12±3.13) and girls (7.82±2.98) was found to be comparable with no statistically significant difference. Fatigue was the most common complaint, with 52 boys (73.24%) and 36 girls (73.47%) reporting it. Pallor was observed in 51 boys (71.83%) and 35 girls (71.43%). MCV, MCH, and MCHC values were comparable in boys and girls whereas red cell distribution width was higher in girls as compared to boys and the difference was statistically significant (p=0.02). Most of the patients (92.5%) had a Mentzer index of more than 13; however, 7.5% of cases were found to have a Mentzer index below 13. Patients with a Mentzer index <13 were advised further investigations to rule out other causes of microcytic hypochromic anemia including beta-thalassemia. Conclusion: The Mentzer index provides a simple and effective tool for differentiating between iron deficiency anemia and thalassemia, especially in resource-limited settings, enhancing diagnostic accuracy and improving patient outcomes.